Test of the Effectiveness of Bilalo Sea Cucumber (Actinopyga Mauritiana) in Pancreatic Beta Cell Repair in Aloxan-Induced Mice (Mus Musculus) - Aris, Anita; Girsang, Ermi; Nasution, Ali Napiah (Universitas Aisyah Pringsewu, 2023)
Introduction diabetes mellitus (DM) is a degenerative disease that occurs due to abnormal carbohydrate metabolism. DM conditions occur when the pancreas is unable to produce insulin or the sensitivity of cell receptors to insulin is very low. The increase in DM occurs when the pancreatic beta cells are unable to produce insulin or the sensitivity of cell receptors to insulin is very low. Damage to pancreatic beta cells can be caused by diabetogenic substances such as alloxan. Teripang bilalo (Actinopyga mauritiana) is a marine animal that has been used as food and medicine. Contains many secondary metabolites, namely flavonoids, alkaloids, glycosides, steroids, and saponins. active compound flavonoids and saponins., research objectives to know the effectiveness of oral administration of teripang billion in reducing blood sugar levels and the ability to repair tissue in pancreatic beta cells seen from hispatology, materials, and methods is an experimental study with 25 mice as subjects. Oral administration of sea teripang bilalo ethanol extract at doses of 100, 200, and 400 mg/kg, positive control by oral administration of glibenclamide, and negative control by administration of Na-CMC then a histopathological examination of the pancreas was performed, research results in the administration of teripang bilalo ethanol extract 400 mg / kg proved to be able to reduce blood sugar levels to 179.4 mg / dl and proved to have an effect on the improvement of pancreatic histology, which is a picture of damage to peripheral islands of langerhans by 1, damage to islands of langerhans less than 50% by 2.4 and damage, conclusions administration of teripang bilalo ethanol extract is proven to reduce blood sugar levels and have an effect on improving pancreatic histology.